2021
DOI: 10.1007/s10529-021-03159-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of the modified cytosine base-editing in the cultured cells of bama minipig

Abstract: Bama minipig is a unique miniature swine bred from China. Their favorable characteristics include delicious meat, strong adaptability, tolerance to rough feed, and high levels of stress tolerance. Unfavorable characteristics are their low lean meat percentage, high fat content, slow growth rate, and low feed conversion ratio. Genome-editing technology using CRISPR/Cas9 e ciently knocked out the myostatin gene (MSTN) that has a negative regulatory effect on muscle production, effectively promoting pig muscle gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Gene sequencing showed that 33.3% (4/12) of single-cell colonies had biallelic ABE-mediated Ato-G conversions at the target locus. This e ciency is comparable to that of CRISPR/Cas9 in generating geneknockout pig cells conducted in our previous studies, suggesting that the ABE system is a practical and feasible approach to generating genetically modi ed porcine cell colonies (Zhu et al 2018;Wei et al 2020;Pan et al 2021). More importantly, RT-PCR and Western blotting tests showed that ABE-mediated single-base mutations in the conservative splice acceptor in the intron 5 of GHR successfully induced exon 6 skipping at the RNA level and gene knockout at the protein level.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Gene sequencing showed that 33.3% (4/12) of single-cell colonies had biallelic ABE-mediated Ato-G conversions at the target locus. This e ciency is comparable to that of CRISPR/Cas9 in generating geneknockout pig cells conducted in our previous studies, suggesting that the ABE system is a practical and feasible approach to generating genetically modi ed porcine cell colonies (Zhu et al 2018;Wei et al 2020;Pan et al 2021). More importantly, RT-PCR and Western blotting tests showed that ABE-mediated single-base mutations in the conservative splice acceptor in the intron 5 of GHR successfully induced exon 6 skipping at the RNA level and gene knockout at the protein level.…”
Section: Discussionsupporting
confidence: 71%
“…PCR amplicons were puri ed using universal DNA puri cation kit (Tiangen) and sent to the GENEWIZ company for Sanger and next generation sequencing according to our previous study (Pan et al 2021). For next generation sequencing, amplicons were ligated to adapters and sequencing was performed on an Illumina MiSeq 2x300bp sequencing platform.…”
Section: Activity Test Of Adenine Base-editing In Cultured Bama Minipig Cellsmentioning
confidence: 99%
See 3 more Smart Citations